Doniphan and Grand Village des Canzas, Doniphan County - Martello, Frank (Kansas State University, The Chapman Center for Rural Studies, 2012)
This is a study concerning the disappearance of the Kansas Indian village of the “Grand Village des Canzes” and the destruction of the town of Doniphan. It is theorized that these two civilizations were created at the same site due to the location by the Missouri river. It is also hypothesized that the Missouri River caused the destruction at both of these establishments.
Frank Martello, “Doniphan and Grand Village des Canzas, Doniphan County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/74.
Keywords: Alexander W. Doniphan; Doniphan County; Doniphan Town Company; Kansa; Atchison and Nebraska Railroad; Commandant of the Missouri River